Racism After Apartheid : Challenges for Marxism and Anti-Racism - Vishwas Satgar (Book collections on Project MUSE., 2019)
Racism after Apartheid, volume four of the Democratic Marxism series, brings together leading scholars and activists from around the world studying and challenging racism. In eleven thematically rich and conceptually informed chapters, the contributors interrogate the complex nexus of questions surrounding race and relations of oppression as they are played out in the global South and global North. Their work challenges Marxism and anti-racism to take these lived realities seriously and consistently struggle to build human solidarities."